MBA UMPSA opens opportunities to improve career and organizational management skills - Noraina Mazuin, Sapuan (UMPSA, 2024)
GAMBANG, 20 August 2023 – Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) is offering the public an opportunity to enrol in its Master of Business Administration (MBA) programme.